Comparison of physical and physiological profiles between elite freestyle men and women wrestlers - Deliceoglu, G.; Tortu, E.; Keles, A.; Cakar, A. N.; Özsoy, H. Ö.; Atalay, T. A. (European Journal of Human Movement, 2023)
This study aims to compare the physical and physiological profiles between elite men and women wrestlers of free style category. The research group consist of twenty-nine men and twenty-one women freestyle wrestlers who camped for performance tests at the Turkish Olympic Preparation Center in Ankara 2 months before the European Wrestling Championship in Budapest on March 28-April 3, 2022. Subjects performed the leg and arm Wingate anaerobic test (anaerobic power and capacity), VO2max (aerobic endurance), Reactive agility, isokinetic and isometric strength test. The results showed that Lower Extremity anaerobic power obtained from men, knee flexor at VO2max, 60°/s and 180°/s peak torque, isometric force values of arm and trunk extensor muscles, are higher than in women (p<0.05). In contrast, upper extremity anaerobic power values seem to be similar (p>0.05). As a result, it can be said that the endurance capacity, isometric, and isokinetic strength parameters are more effective than the force parameter in gender. These results can be used by coaches, strength and conditioning specialists, and sport scientists to create a comprehensive physical and physiological profile of wrestlers that will help them adapt their training programs.